Critical reading and writing for postgraduates - Wallace, Mike; Wray, Alison (Thousand Oaks, California : Sage Publications, Incorporation, 2021)
Focusing on critical reading and self-critical writing, this book is suitable for postgraduate students and early-career academics. It contains tools for analysing texts and structuring critical reviews, and incorporates exercises and worked examples drawn from the social sciences
Part one: Becoming a critical reader and self-critical writer: What it means to be critical -- Making a critical choice -- Getting started on critical choice -- A First Look: Interrogating Abstracts -- Getting started on critical reading -- Getting started on self-critical writing -- Creating a comparative critical summary -- Part two: Developing an In-Depth Analysis -- A Mental Map for navigating the Literature -- Tools for Thinking and Ways of Thinking -- Reasons for Conducting the research -- Knowledge Claims and their key characteristics -- Developing a critical analysis of a text -- A worked example of a critical analysis -- Developing your argument in writing a crtical review of a text -- Part Three: Putting your critical review to work -- Focusing and building up your critical literature review -- Integrating critical literature reviews into your dissertation -- Critical Literature Reviews in Alternative dissertation structures -- Tools for structuring a dissertation -- Using the Literature in Research Papers, Oral Presentations and Posters -- Developing Advanced Writing Skills.
Includes bibliographical references and index.
Keywords: CRITICAL THINKING -- STUDY AND TEACHING